The Impact of social media on Culture Formation (Case Study of Instagram Stories in The Establishment of Travelling Hobby) - Shin Hajin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tanjungpura, 2022)
The purpose of this study is to investigate the effect of social media, specifically Instagram stories on culture formation of travelling as hobbies. The data was collected using a standardized questionnaire that was distributed to a sample of 150 people and tested using stepwise multiple regression analysis. The study sample includes Instagram users who view Instagram stories on a daily basis. According to the research, Instagram stories have a significant impact on impulse buying of travel products because of the features that activate and appeal to buyers toward tourist places and travel products. Instagram stories improve customer hedonic motivation, website quality, situational variable, and diversity seeking. The data, on the other hand, imply that trust is a factor that Instagram stories cannot provide in order to attract customers to make impulse purchases of tourism locations and travel products. The findings imply that social media may generate a new trend that leads to hobbies but does not form culture. Marketers that use social media to sell their travel product should develop a product or a campaign on social media that is not necessarily a trend but rather a cultural phenomenon.